Evidences for the action mechanism of angiotensin II and its analogs on Plasmodium sporozoite membranes. (March 2016) - Torres, Marcelo Der Torossian; Silva, Adriana Farias; Alves, Flávio Lopes; Capurro, Margareth Lara; Miranda, Antonio; Cordeiro, Rodrigo Maghdissian; Oliveira Junior, Vani Xavier
Abstract : Malaria is an infectious disease responsible for approximately one million deaths annually. Oligopeptides such as angiotensin II (AII) and its analogs are known to have antimalarial effects against Plasmodium gallinaceum and Plasmodium falciparum . However, their mechanism of action is still not fully understood at the molecular level. In the work reported here, we investigated this issue by comparing the antimalarial activity of AII with that of (i) its diastereomer formed by onlyd ‐amino acids; (ii) its isomer with reversed sequence; and (iii) its analogs restricted by lactam bridges, the so‐called VC5 peptides. Data from fluorescence spectroscopy indicated that the antiplasmodial activities of both all‐D ‐AII and all‐D ‐VC5 were as high as those of the related peptides AII and VC5, respectively. In contrast, retro ‐AII had no significant effect against P. gallinaceum . Conformational analysis by circular dichroism suggested that AII and its active analogs usually adopted a β‐turn conformation in different solutions. In the presence of membrane‐mimetic micelles, AII had also a β‐turn conformation, while retro ‐AII was random. Molecular dynamics simulations demonstrated that the AII chains were slightly more bent than retro ‐AII at the surface of a model membrane. At the hydrophobic membrane interior, however, the retro ‐AII chain was severely coiled and rigid. AII was much more flexible and able to experience both straight and coiled conformations. We took it as an indication of the stronger ability of AII to interact with membrane headgroups and promote pore formation. Copyright © 2016 European Peptide Society and John Wiley & Sons, Ltd. Abstract : Antiplasmodial activities of all‐D ‐angiotensin II (AII) analogs were as high as those of the relatedl ‐peptides. In contrast, retro ‐AII had no significant effect against Plasmodium gallinaceum. Circular dichroism studies suggested that all peptides usually adopted β‐turn conformation in different means, except for retro ‐AII in membrane‐mimetic micelles, which was random. Molecular dynamics simulations demonstrated that the AII chains were slightly more bent than retro ‐AII at the surface of a model membrane. At the hydrophobic membrane interior, however, the retro ‐AII chain was severely coiled and rigid. AII was much more flexible and able to experience both straight and coiled conformations. We took it as an indication of the stronger ability of AII to interact with membrane headgroups and promote pore formation.